Study on Strength Characteristics of Binary Blend Self Compacting Concrete Using Mineral Admixtures - J. Prasannaa Venkatesh, G; S.Vivek, S; Dhinakaran, G (International Journal of Engineering and Technology, 2018)
Self-compacting concrete (SCC) is the flowable concrete which tends to fill the formwork under its weight without external compaction. In the present research, 9 different SCC mixes in binary blend along with control SCC and conventional vibrated concrete (CVC) mixes were developed. In binary combination, cement was partially replaced by SF from 7 to 21%, MK from 10 to 30% and GGBS from 20 to 60%. For the above 9 combinations of SCC mixes, the basic rheological properties test namely slump flow and T500 were carried out in the fresh state of SCC. The flowability was achieved using Superplasticizer and viscosity modifying admixture (VMA), added by the percentage of the weight of cement. In hardened state, the compressive strength of the cube specimens and the split tensile strength of the cylinder specimens were carried out.Â Â